Estudo da Percepcąõ Ambiental dos Moradores do Município de Pains sobre o Parque Natural Municipal Dona Ziza - Silva, Lorena Lorrayne Da; Teixeira, Catarina [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2017)
The aim of this study was to analyze the environmental perception of the Pains of residents of the Municipal Park Dona Ziza. It was also found the use of park space for their visitors, the environmental behavior of the same and identified, finally, the strengths and weaknesses found in the park were discussed. To conduct this research, questionnaires were given to residents of the city of Pains, MG . Was conducted content analysis on the data collected showed that the environmental awareness of the residents, which can provide support for the conservation and sustainability of the park. Spaces like Dona Ziza Park are important recreational areas and on the other hand, requires constant maintenance of their equipment and to fulfill its function promoting environmental education activities to its visitors.
Study of the environmental perception of the dwellers of the municipality of pains on the municipal natural park dona ziza
Keywords: Dona Ziza Park; Environmental Education; Environmental Perception